When and why do countries break their national fiscal rules? - Wolf Heinrich Reuter (Sachverständigenrat zur Begutachtung der Gesamtwirtschaftlichen Entwicklung, 2017)
This paper identifies determinants of compliance with various types of national numerical fiscal rules. Based on 51 fiscal rules in 20 EU member states from 1995 to 2015, the analysis identifies determinants among specific rule characteristics and their fiscal frameworks, as well as their political, (socio-)economic and supranational environments. While the average compliance across all rules and countries is around 50%, compliance with rules constraining stock (rather than flow) variables, set out in coalitional agreements, as well as rules covering larger parts of general government finances is significantly higher. Furthermore, independent monitoring and enforcement bodies (issuing real-time alerts) turn out to be significantly associated with a higher probability of compliance. Several theories of the deficit bias of governments due to government fragmentation, decentralization and political budget cycles are also significant with regards to compliance with fiscal rules. However, neither the economic environment or business cycle, nor forecast errors (except for an unexpectedly higher primary balance) on average seem to play a significant role.
Keywords: E62; H60; H11; 330; National Numerical Fiscal Rules; Compliance; Fiscal institutions; Deficit Bias